STUDENTS’ PERCEPTION ABOUT THE ENGLISH LEARNING AT SMA NEGERI 3 LAKUDO - Dunifa, La; Zamihu, Juamdan Zamha; Rianti, Rianti (English Education Journal, 2023)
The problem statement of this research was what are students’ perception about the English learning at SMA Negeri 3 Lakudo. The objective of this research was to determine students’ perception about the English learning at SMA Negeri 3 Lakudo. This research used the qualitative research design. The subject of this research was the class XI.IPA SMA Negeri 3 Lakudo in the academic year 2022/2023. The data was obtained by observation and interview then was analyzed by the researcher with three steps; data reduction, data display, and draw conclusion or verification. This research found that students’ perception about the English learning at SMA Negeri 3 Lakudo. Those were that students unpleasant feeling, students were not interested, students often feel bored in learning English and students often felt lazy in learning English.